Apparent difference in fatalities between Central Europe and East Asia due to SARS-COV-2 and COVID-19: Four hypotheses for possible explanation. (November 2020) - Yamamoto, Naoki; Bauer, Georg
Abstract: The comparison of the numbers of cases and deaths due to SARS-CoV-2/COVID-19 shows that people in Central Europe are much more affected than people in East Asia where the disease originally occurred. Trying to explain this difference, this communication presents four hypotheses that propose the following reasons for the observed findings: 1) Differences in social behaviors and cultures of people in the two regions; 2) Possible outbreak of virulent viruses in Central Europe due to multiple viral infection, and the involvement of immuno-virological factors associated with it, 3) Possibility of corona resistance gene mutation occurring among East Asians as a result of long-term co-evolution of virus and host, and 4) possible involvement of hygienic factors. Direct or indirect supportive evidences for each one of our hypotheses are presented and experimental approaches for their evaluation are discussed. Finally, we suggest that the dynamics of the pandemic also shows that the problems of the new coronavirus can be overcome due to people's awareness of the epidemics, rational viral diagnostics and a high level of medical care.